2018
DOI: 10.24036/wra.v6i2.102509
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Retaliation dan Gender Terhadap Niat Melakukan Whistle Blowing

Abstract: This study aims to empirically examines the influence of retaliation on whistleblowing intentions, the influence of gender on whistleblowing intention, and the influence of retaliation and gender interaction on whistleblowing intention. This study used a quasi-experimentation design. The data of this study were collected by a survey questionnaires administered on 122 accounting students from a university in Padang, the capital of West Sumatra. The data were analyzed using ANOVA. The results of this study show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…Terlepas dari risiko yang muncul, fakta bahwa Nurhayati yang merupakan seorang perempuan berani bertindak untuk melaporkan kecurangan yang terjadi merupakan hal yang luar biasa karena stereotip yang terbentuk dalam masyarakat adalah laki-laki merupakan individu yang lebih berani sehingga dianggap akan lebih cenderung melaporkan kecurangan yang terjadi (Near & Miceli, 1985). Laki-laki dianggap lebih suka terhadap tantangan ketika menemukan sebuah kesalahan, tidak seperti perempuan yang memikirkan keadaan dirinya sendiri di lingkungan pekerjaan (Saputra & Dwita, 2018).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Terlepas dari risiko yang muncul, fakta bahwa Nurhayati yang merupakan seorang perempuan berani bertindak untuk melaporkan kecurangan yang terjadi merupakan hal yang luar biasa karena stereotip yang terbentuk dalam masyarakat adalah laki-laki merupakan individu yang lebih berani sehingga dianggap akan lebih cenderung melaporkan kecurangan yang terjadi (Near & Miceli, 1985). Laki-laki dianggap lebih suka terhadap tantangan ketika menemukan sebuah kesalahan, tidak seperti perempuan yang memikirkan keadaan dirinya sendiri di lingkungan pekerjaan (Saputra & Dwita, 2018).…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini tidak sejalan dengan penelitian yang dilakukan oleh (Dananjaya & Mawardi (2018) dan Saputra & Dwita (2018) yang menyatakan bahwa gender memiliki pengaruh terhadap intensi whistleblowing.…”
Section: Pengaruh Gender Terhadap Intensi Whistleblowingunclassified
“…However, if an individual has a high sense of organizational commitment, the threat of retaliation will not have an effect and he will proceed to report the fraud. The research conducted by Kusnadi and Ariyanto (2018) and Saputra and Dwita (2018) revealed that there is a negative effect of retaliation on a personal intention to act whistle-blowing. Meanwhile, organizational commitment greatly affects individual intention in performing whistle-blowing.…”
Section: Effect Of Organizational Commitment In Moderating the Relationship Of Retaliation With Whistle-blowing Intentionmentioning
confidence: 99%
“…It is a statemenet made by colleagues or managers against employees who have reported violations (Joy, 2014). According to study results, Saputra and Dwita (2018) found that retaliation has an adverse effect on the intention to do whistleblowing. It means that the lower the level of retaliation, the higher the intention to do whistle-blowing.…”
Section: Introductionmentioning
confidence: 99%
“…Women's Studies Encyclopedia mendefinisikan Gender sebagai sebuah konsep kultural yang berusaha membuat perbedaan peran, perilaku mentalis, dan karakteristik emosional pria dan wanita yang berkembang dalam masyarakat. (Saputra & Dwita, 2018). Gender juga dapat diartikan sebagai perbedaan perilaku pria dan wanita yang terbentuk dari proses sosial dan kultural.…”
Section: Genderunclassified